Understanding landscape architecture industry needs: a preliminary review of graduates Communication Proficiency Model (CPM) / Amir Zuhairy Alias ... [et al.] - Alias, Amir Zuhairy; Abdul Malek, Nurhayati; Othman, Noriah; Mohamed, Noralizawati (2021)
Communication is a fundamental part of the working environment that comprises interpersonal relations and communication between groups and individuals and other social interactions within the active community. Communication and soft skills have become an important issue due to the lack of study and development, especially in the Landscape Architectural practice. It can be seen that the lack of communication and soft skills by current graduates has affected employability leading to a large quantity of unemployment and lack of advancement within the landscape industry. Hence, to keep up with the current trends of what employers seek within these landscape architecture graduates, it is believed that a paradigm shift in the training of students must take into account the development of Communication Skills within the curriculum to help aid the development of graduate employability skills. A method of assessing communication skills is also required to rate a Landscape Architect’s level of communication competence to further enhance the graduates’ career in the industry.